Analisis Komunikasi Pemasaran Pada Campaign Proyek Lestari Brodo - Wedantha, Ida Bagus Aditya Giri; Nugrahani, Rah Utami (eProceedings of Management, 2023)
The Indonesian fashion industry has now begun to develop with the presence of various local fashion brands with diverse models, such as clothes and shoes. As the fashion industry developed in Indonesia, people began to look at local brands, and one of the most famous local shoe brands in Indonesia was Brodo. With the concept of eco-friendly breakthrough, which is utilizing leftover materials into new products, Brodo initiated a project called Project Lestari with the goal of being an initiative for the environment. The purpose of this study is to find out the effective marketing communication strategy Brodo undertook during the Lestari Project campaign. This study uses qualitative research methods. With data collection through interviews, observation, and documentation. Data abstraction techniques use source triangulation techniques. This study used the effective marketing communication theory proposed by Machfoedz. Research results show that Brodo's messaging strategy already has communication goals and uses creative forms of rational and emotional messaging. In his media strategy, Brodo uses direct and indirect communication channels such as Instagram, websites, and YouTube. Brodo did not know the consumer gap that arose from Project Lestari X Dian Sastrowardoyo.Keyword-local brand, effective marketing communication, message strategy, media strategy